The first three terms of sequence are 9 , 6 , 3
Solution:
Given the recursive function f(n) = f(n - 1) - 3
Where f(1) = 9
To find: First three terms of sequence
Substitute n = 2 , n = 3 and n = 4 in given recursive function
When n = 2
f(n) = f(n - 1) - 3
f(2) = f(2 - 1) - 3
f(2) = f(1) - 3
f(2) = 9 - 3 = 6
f(2) = 6
Thus second term is 6
When n = 3
f(3) = f( 3 - 1) - 3
f(3) = f(2) - 3
f(3) = 6 - 3 = 3
f(3) = 3
Thus the third term is 3
When n = 4
f(4) = f( 4 - 1) - 3
f(4) = f(3) - 3
f(4) = 3 - 3
f(4) = 0
Thus the fourth term is 0
Thus first three terms of sequence are 9 , 6 , 3